2022
DOI: 10.1029/2021jb022994
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Artifacts in Multi‐GNSS Precise Point Positioning Time Series

Abstract: The Global Navigation Satellite System (GNSS) data are widely used for Earth system observations, for example, solid earth, atmosphere, and hydrosphere (Freymueller, 2017). The US GNSS, called Global Positioning System (GPS), plays the most important role in this research because of the availability of long-term data and observation processing tools, advanced processing methodology, and high-accuracy products sufficient for most applications. Furthermore, GPS is complemented by the Russian GLONASS, which is ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
(101 reference statements)
0
2
0
Order By: Relevance
“…All selected stations belong to the Multi-GNSS Experiment (MGEX) pilot project (Kouba 2009;Montenbruck et al 2017) and ensure tracking of three GNSS systems to analyze system-specific clock errors. Zajdel et al (2020Zajdel et al ( , 2022 identified system-specific errors emerging from different aliasing, revolution periods of satellites, and multipath effects in multi-GNSS (GPS, GLONASS, Galileo) solutions. This raises the question of whether similar systematic errors can be identified in the multi-GNSS clock parameters.…”
Section: Introductionmentioning
confidence: 99%
“…All selected stations belong to the Multi-GNSS Experiment (MGEX) pilot project (Kouba 2009;Montenbruck et al 2017) and ensure tracking of three GNSS systems to analyze system-specific clock errors. Zajdel et al (2020Zajdel et al ( , 2022 identified system-specific errors emerging from different aliasing, revolution periods of satellites, and multipath effects in multi-GNSS (GPS, GLONASS, Galileo) solutions. This raises the question of whether similar systematic errors can be identified in the multi-GNSS clock parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate modeling of non‐gravitational force is required for the precise orbit determination of LEO satellites (Hackel et al., 2016; Kang et al., 2006; Montenbruck, Hackel, & Jäggi, 2018; Wu et al., 1991), SLR satellites (Appleby et al., 2016; M Pearlman, Arnold, et al., 2019; Zajdel et al., 2022), and GNSS satellites (D. Arnold et al., 2015; Bury et al., 2020; Duan et al., 2020; Montenbruck et al., 2014; Zhao et al., 2022). Solar radiation pressure and atmospheric drag are the two most important non‐gravitational forces acting on LEO satellites.…”
Section: Introductionmentioning
confidence: 99%